The Knack of Selling: scientific salesmanship, relational themes and military metaphors in early marketing thought. (11th June 2020) - Tadajewski, Mark; Jones, D.G. Brian
Abstract : Purpose: The purpose of this paper is to provide an historical analysis of an important early contribution to the history of marketing thought literature – the six-book series titled The Knack of Selling – which was published in 1913 and intended as an early training course for salesmanship. Design/methodology/approach: This research utilized a close, systematic reading of The Knack of Selling series and places it in the professional and intellectual context of the early twentieth century. Books published about marketing are primary source materials for any study of the history of marketing thought. In this case, The Knack series constitutes significant primary source material for a study of early thinking about personal selling. Findings: Echoing A.W. Shaw, Watson offers a more sophisticated interpretation of the "one best way" approach associated with Frederick Taylor. Watson's advice did not entail the repetition of canned sales talks to each customer. His vision of practice was more complicated. Sales presentations were temporally and locationally relative. They were subject to ongoing evolution. As the marketplace changed, as customer needs and interests shifted, so did organizational and salesperson performances. To keep sales talks relevant to the consumer, personnel were encouraged to undertake rudimentary ethnographic research and interviews. Unusually, there is oscillation in the way power relations between marketer and customer were described. While relational themes are present, so are military metaphors. Originality/value: This is the first systematic reading of The Knack of Selling that has been produced. It is an important contribution to the literature inasmuch as this book set is not in wide circulation. The material itself was significant as an input into scholarship subsequently hailed as seminal within sales management.